PROBLEMATIKA GURU PENDIDIKAN AGAMA ISLAM DALAM MENGELOLA PEMBELAJARAN PASCA COVID-19 DI SD INPRES JONGAYA 1 KOTA MAKASSAR - Margiono, Margiono; Malli, Rusli; Wahdaniya, Wahdaniya (LPPM Universitas Islam 45, 2024)
The problems faced by Islamic Religious Education Teachers in managing post-Covid-19 learning at SD Inpres Jongaya 1 are behavior and character, such as students' lack of discipline in attending lessons, lack of a culture of shame, namely shame if they break the rules. For example: embarrassed to come late, ashamed not to picket, ashamed not to do homework and so on. Supporting and inhibiting factors for Islamic religious education teachers in managing learning at SD Inpres Jongaya 1, namely: supporting factors are, such as the school providing a Wi-fe network, good teacher relations, and adequate school facilities and the inhibiting factor is that the teacher is not too able to know the characters of each student, the assessor that underlies the needs of students has not been conveyed in the learning process and lacks infrastructure. The teacher's efforts in overcoming problems in managing post-covid-19 learning at SD Inpres Jongaya 1, namely searching for and digging up information through training or by using search media to get updated information regarding how to manage learning and the development of the learning curriculum at SD Inpres Jongaya 1.